The impact of emotional intelligence, cross-functional teams and interorganizational networks on operational effectiveness (2023)
Purpose This article aims to examine the influence of emotional intelligence on cross-functional teams, the formation of interorganizational networks and the impact of all three dimensions on operational effectiveness. Design/methodology/approach The ana